Policy Language in Restoration Ecology. Issue 1 (26th November 2013) - Jørgensen, Dolly; Nilsson, Christer; Hof, Anouschka R.; Hasselquist, Eliza M.; Baker, Susan; Chapin, F. Stuart; Eckerberg, Katarina; Hjältén, Joakim; Polvi, Lina; Meyerson, Laura A.
Abstract Relating restoration ecology to policy is one of the aims of the Society for Ecological Restoration and its journal Restoration Ecology. As an interdisciplinary team of researchers in both ecological science and political science, we have struggled with how policy‐relevant language is and could be deployed in restoration ecology. Using language in scientific publications that resonates with overarching policy questions may facilitate linkages between researcher investigations and decision‐makers' concerns on all levels. Climate change is the most important environmental problem of our time and to provide policymakers with new relevant knowledge on this problem is of outmost importance. To determine whether or not policy‐specific language was being included in restoration ecology science, we surveyed the field of restoration ecology from 2008 to 2010, identifying 1, 029 articles, which we further examined for the inclusion of climate change as a key element of the research. We found that of the 58 articles with "climate change" or "global warming" in the abstract, only 3 identified specific policies relevant to the research results. We believe that restoration ecologists are failing to include themselves in policy formation and implementation of issues such as climate change within journals focused on restoration ecology. We suggest that more explicit reference to policies and terminology recognizable to policymakers might enhance the impact of restoration ecology on decision‐making processes.